Digital comic of Indonesia's historical heritage for 5th-grade students: a study of cognitive learning outcomes - Yulina Ismiyanti; Andarini Permata Cahyaningtyas; Radna Andi Wibowo (Jurnal Ilmiah Pendidikan Dasar, 2025)
The need for engaging and context-based learning media is essential to improve students’ understanding of national history and heritage. This study aims to develop an innovative digital comic on Indonesian historical heritage for elementary school students and evaluate its feasibility, practicality, and effectiveness. The research adopts a Research and Development (R&D) approach using the ADDIE model (Analyze, Design, Develop, and Implement). The population in this study consists of 48 fifth-grade students at SDN Kayuapu, a public elementary school in Indonesia. The entire population of 48 students was selected as the sample using purposive sampling, divided into two classes for implementation. Data collection techniques include expert validation sheets, teacher and student questionnaires, and pretest-posttest instruments. The data were analyzed using descriptive statistics for feasibility and practicality, and an independent sample T-test to assess the effectiveness of the digital comic. The results showed that the product is highly feasible, based on expert evaluation; practical, according to positive teacher and student responses; and effective, with a statistically significant improvement in student learning outcomes (p < 0.05). The study implies that digital comics can be a powerful medium for enhancing students’ historical literacy and cognitive engagement in line with 21st-century learning objectives.